2015
DOI: 10.1017/s0144686x15001397
|View full text |Cite
|
Sign up to set email alerts
|

Family care-giving and living arrangements of functionally impaired elders in rural China

Abstract: China has seen a rapid decline of the traditional multi-generational household and an increase in rural-to-urban migration, raising concerns about a possible breakdown of the informal support system. Against this background, the paper looks at family care-giving (or the absence thereof) to parents in three different living arrangements: with any child or child-in-law (co-resident); independent with at least one child living in the same community (networked); and without any children in either the household or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…This study investigated the preferred care arrangements among the Chinese older population. Most of the existing Chinese studies have focused on the actual utilization of social care and its determinants, but less is known about people's care preferences (Gruijters, 2017;Lu, Liu, & Piggot, 2015). A systematic review conducted by Lehnert et al (2019) identified five China-based studies, among which four focus on Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated the preferred care arrangements among the Chinese older population. Most of the existing Chinese studies have focused on the actual utilization of social care and its determinants, but less is known about people's care preferences (Gruijters, 2017;Lu, Liu, & Piggot, 2015). A systematic review conducted by Lehnert et al (2019) identified five China-based studies, among which four focus on Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…When older people make care plans for the future, offspring seem to be the most important social support resources under consideration. It is also interesting to note that while living with a spouse is an important predictor of actual utilization of family care (Gruijters, 2017), it makes little difference to older people's care preferences. This once again shows that the determinants of actual utilization of care do not necessarily overlap with those of preferred care arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a viable option for some adult children to take turns providing care or sharing the caring tasks. In comparison, a spouse is usually the main caregiver, if not the sole caregiver, and thus is fully exposed to the health risks of caregiving (Gruijters, 2017). Therefore, our second hypothesis can be summarised as follows: H2: The protective effects are stronger among older people receiving informal care from their children.…”
Section: Informal Care and Trajectories Of Functional Limitationsmentioning
confidence: 99%
“…Historically, besides spouses, both adult sons and daughters played critical roles in providing care to frail elderly relatives when the multigenerational household was the predominant form. This is still the case in rural China, where formal long-term care facilities are notably absent, leaving sons and daughters-in-law to co-reside with and care for their elders (Gruijters, 2017). Evidence shows that, for the collective welfare of the household, daughters are more likely to provide direct eldercare ( i.e.…”
Section: Informal Eldercare In Chinamentioning
confidence: 99%